Enhancement of Pro-inflammatory Cytokine by Partial Purified Lipopolysaccharide Extracted from Invasive Klebsiella Pneumoniae - Yossef, Hanaa Saleem (Al-Nahrain Journal of Science, 2018)
Lipopolysaccharide was extracted from invasive local isolate Klebsiella pneumonia previously isolated from neonate blood samples. LPS was extracted by phenol hot water method and partial purified by gel filtration chromatography on sepharose CL-6B gel. The results showed that the percentage of carbohydrate amount in the partially purified LPS extract was 9.5% while the percentage of protein in the same extract was 0.06% with no nucleic acids. Intravenous administration of (0.1and1)µg/kg of partial purified LPS in the rabbit led to increase body temperature in dose dependent manner (38.8° and 40.2°)C respectively. Intraperitonial administration with the dose 10µg/mouse cause an increasein serum cytokine (IL-1α, IL-6 and TNFα) level after 4 hr of the injection. Conclusion: LPS extracted from pathogenic isolate of K.pneumoniae with high purity, has immunomodulator effect by increasing serum cytokine (IL-6 & IL-1α) level which play a role in the elevation of body temperature, and TNFα after 4hr of intraperitonial administration of LPS.